Towards Equality: Radio Braille Surabaya's Communication Strategy in Promoting Disability Awareness - Natalia, Wahyu Kristian; Widiatmojo, Radityo; Nugroho, Rio Satria; Fatikh, M. Alfin (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2024)
Promoting inclusivity requires the vital aspect of ensuring equality for people with disabilities in information dissemination. As one of the mass media, the radio community contributes to knowledge and information dissemination to promote equality. Radio Braile Surabaya is a radio community providing a forum for information exchange. It aims to empower a source of knowledge to promote inclusivity, equality, and disability awareness in urban society. Therefore, this study investigates the strategies of content production of Radio Braile Surabaya to promote equality and inclusivity for disabled people, especially people with visual impairments. This study applied a qualitative approach with a case study as the framework. The data was collected through in-depth interviews with purposive samplings. The interviews were conducted with three key informants who manage and organize Radio Braile Surabaya. The result shows that the strategies include collaborative content planning, underlining the public infrastructure for disabled people, and emphasizing audio-rich content production and storytelling. This study underscores the importance of the radio community as a tool for empowering marginalized groups, such as people with disabilities, by providing equal information dissemination through accessible content.